Assessment of the possible interactions between soil and plant water status in a Vitis vinifera cv. Merlot vineyard - Van Zyl, Albertus J. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2014.